Sustaining family bakeries in Pakistan: The role of internal marketing and entrepreneurship - Warraich, U. A.; Dos-Santos, M. J. P. L. (Ecocycles, 2024)
Nowadays, climatic change challenges, consumer expectations, and concerns toward sustainability lead firms to consider responsible strategies for internal marketing and entrepreneurial orientation that contribute to competitive advantage and economic and environmental performance. This paper analyses the direct impact of internal marketing and entrepreneurial orientation on innovation and sustainability within the context of family businesses in the manufacturing sector in bakeries in Sindh Province in Pakistan. Information and data were obtained from 404 questionnaires applied in these firms during 2023. The methods include Partial Least Squares Structural Equation Modelling to evaluate the measurement, structural models, and respective variables. Results confirm a significant direct influence of internal marketing on entrepreneurial orientation and innovation towards the sustainability of bakeries firms and emphasise the mediating role of entrepreneurial orientation toward sustainability. Despite that, the firms haven’t improved significantly sustainable production practices during the last three years. On the other hand, the unit cost of bakery production hasn’t decreased during this period due to the reduction of energy or water use. Other results also confirm a significant concern with the customer’s needs, but without putting in practice more quality in the production process or reducing the relative production costs (at constant prices). However, bakeries firms must directly address sustainability in all production and customer sales processes, namely reducing energy inputs and meeting consumers’ needs concerning sustainable needs and goals. This study’s significance lies in its contribution to the existing body of literature by illuminating the intricate pathway of relationships between internal marketing, entrepreneurial orientation toward sustainability, and innovation and sustainability. A future direction involves extending this model’s applicability by examining its validity in other industries and service sectors, enriching the breadth of understanding beyond manufacturing industries.